9 SOR MODEL: A MULTI-STAKEHOLDER APPROACH TO SUS-TAINABLE LOCAL DEVELOPMENT IN THAILAND - Bajrawan Nuchprayool (PEOPLE: International Journal of Social Sciences, 2026)
This research addresses the systemic challenge of policy discontinuity in Thai local development, which is frequently exacerbated by political volatility and transitions in leadership. The primary objective is to evaluate the institutionalization of multi-stakeholder partnerships as "Development Partnerships" capable of stabilizing public service delivery and area-based policies within inherently unstable political environments. Utilizing a qualitative action research framework and an area-based management lens, the study investigates the "9 Sor" (9 S) collaborative mechanism. The investigation focuses on five pilot provinces- Chiang Rai, Nakhon Sawan, Khon Kaen, Trat, and Phatthalung- where diverse stakeholders from civil society, academic institutions, and autonomous state agencies were integrated into a unified governance ecosystem during the 2024-2025 period. The findings demonstrate that these multi-stakeholder networks function as a resilient "Social Infrastructure" that mitigates the risks associated with political shifts. This resilience is attributed to the transition from vertical governmental hierarchies to a "Flat Ecosystem," the formalization of civil society’s legal status through administrative regulations, and the implementation of fiscal innovations. Specifically, the establishment of joint funding mechanisms between local governments and health agencies serves as a crucial budgetary buffer against partisan political interference. Consequently, the research outcomes advocate for a paradigm shift in the legal and constitutional recognition of "Development Partners," moving beyond temporary cooperation toward permanent, stable public policy institutions. Future scope for this research includes the development of a "Collaboration Maturity Index" and a comparative analysis of tax incentives for civil society organizations to foster a conducive legal environment for sustainable developmental partnerships across the ASEAN region.